Early osteogenic differentiation of human dental stem cells by gelatin/calcium phosphate- Punica granatum nanocomposite scaffold - Atefeh Abedi; Simin Sharifi; Mahsa Baghban Shaker; Maryam Jalili; Solmaz Maleki Dizaj; Elaheh Dalir Abdolahinia (BMC Biotechnology)
Abstract Background Tissue engineering for bone regeneration aims to heal severe bone injuries. This study aimed to prepare and assess the early osteogenic differentiation effects of a gelatin/calcium phosphate- Punica granatum nanocomposite scaffold on stem cells from human exfoliated deciduous (SHED) and human dental pulp stem cells (HDPSCs). Methods The electrospinning method was used to prepare a gelatin/calcium phosphate nanocomposite scaffold containing pomegranate (Punica granatum) extract. The physicochemical properties of the scaffold were evaluated. The effect of the scaffold on the selected cells was done by the cell viability evaluation. A special alkaline phosphatase (ALP) kit was utilized to investigate the early osteogenic differentiation effects of the prepared scaffold on HDPSCs and SHED. Results The results showed that the scaffold had uniformly accumulated in the networked form. Besides, the prepared scaffold did not have beads (structural defects). No new interactions were observed in the spectroscopic spectra of the scaffold and these peaks showed the successful formation of the fibrous nanocomposite as well. Furthermore, cell viability percentage was significantly higher for the scaffold compared with the control group (cells without any material) for both HDPSCs and SHED. Early osteogenic differentiation results specified that the ALP activity was significantly higher for the scaffold compared with the control group (cells without any material) for both HDPSCs and SHED. Conclusion The appropriate physicochemical assay and cellular results (cell viability and early osteogenic differentiation) for the prepared fibrous nanocomposite showed that the use of this nanocomposite can be considered in the construction of various scaffolds in bone and dental tissue engineering.